A comparison of the wake structures of scale and full-scale pedalling cycling models - Crouch, T. N.; Burton, D.; Venning, J. A.; Thompson, M. C.; Brown, N. A. T.; Sheridan, J. (Procedia Engineering, 2016)
This paper presents a novel approach to better understand the unsteady aerodynamics associated with a dynamically pedalling cyclist. Using high resolution Particle Image Velocimetry (PIV) in a water channel, the large-scale wake structure is analysed for various phases of the crank cycle of a 1:4.5 scale-model cyclist/bicycle under both static and pedalling conditions. Both quasi-steady and dynamic pedalling leg results are compared with detailed velocity field surveys made in the wake of a full-scale pedalling cyclist mannequin of similar geometry and position in a wind tunnel. A time-averaged and phase-averaged analysis of the various flow regimes that occur throughout the pedal stroke shows good agreement between scale-model and full-scale mannequin investigations. This highlights the robustness of the formation of the primary wake flow structures when subjected to varying Reynolds number, bicycle/rider geometry and quasi-steady/dynamic pedalling conditions.